\(a,n+9⋮n+2.\)
\(\Rightarrow\left(n+2\right)+7⋮n+2.\)
mà \(n+2⋮n+2\Rightarrow7⋮n+2\Rightarrow n+2\in U_{\left(7\right)}=\left\{1;7\right\}.\)
\(\Rightarrow n\in\left\{-1;-9\right\}.\)
Vậy..........
\(b,2n+9⋮n-1.\)
\(\Rightarrow\left(2n-2\right)+11⋮n-1.\)
\(\Rightarrow2\left(n-1\right)+11⋮n-1.\)
mà \(2\left(n-1\right)⋮n-1\Rightarrow11⋮n-1\Rightarrow n-1\in U_{\left(11\right)}=\left\{1;11\right\}.\)
\(\Rightarrow n\in\left\{2;12\right\}.\)
Vậy..........
\(c,3n+5⋮2n+1.\)
\(\Rightarrow2\left(3n+5\right)⋮2n+1.\)
\(\Rightarrow6n+10⋮2n+1.\)
\(\Rightarrow\left(6n+3\right)+7⋮2n+1.\)
\(\Rightarrow3\left(2n+1\right)+7⋮2n+1.\)
mà \(3\left(2n+1\right)⋮2n+1\Rightarrow7⋮2n+1\Rightarrow2n+1\in U_{\left(7\right)}=\left\{1;7\right\}.\)
\(\Rightarrow n\in\left\{0;3\right\}.\)
Vậy..........
a) n+9⋮n+2= (n+2)+7⋮n+2
=> n+2 ∈ Ư(7)={1;7}
ĐK: n ∈ N
Nếu n+2=1⇒n=1-2=-1 (vì -1∉ N⇒loại)
n+2=7⇒n=7-2=5 (vì 5 ∈ N⇒chọn)
Vậy n=5
b)2n+9⋮n-1=(n-1)+(n-1)+11⋮n-1
⇒ n-1 ∈ Ư(11)={1;11}
ĐK: n∈ N
Nếu n-1=1⇒n=1+1=2 (vì 2∈N⇒chọn)
n-1=11⇒n=11+1=12 ( vì 12 ∈ N⇒chọn)
Vậy n={2;12}
c)3n+5⋮2n+1=(n+1)+(n+1)+(n+1)+2⋮(n+1)+n
ĐK: n∈ N
⇒ n ∈ Ư(2)={1;2}
⇒ n=1(thỏa mãn)
n=2(thỏa mãn)
Vậy n={1;2}